2013
DOI: 10.1016/j.procbio.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic adsorption and covalent immobilization of Candida antarctica lipase B on mixed-function-grafted silica gel supports for continuous-flow biotransformations

Abstract: HighlightsPhenyl-/aminoalkylsilane-grafted silica gels were used as supports for CaLB.Adsorption onto mixed-function-grafted silica supports resulted in active CaLB.CaLB adsorption and glutardialdehyde cross-linking resulted in enhanced durability.The novel CaLB biocatalysts were used in kinetic resolutions of a secondary alcohol and an amine.The novel CaLBs were robust biocatalysts in continuous-flow biotransformations. AbstractAdsorption onto solid supports has proven to be an easy and effective way to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 36 publications
2
48
0
5
Order By: Relevance
“…Ideal properties for immobilization support include chemical and mechanical stability, hydrophilicity, inertness toward enzymes, ease of derivatization, biocompatibility, resistance to microbial attack, and a large surface area. Among the many organic and inorganic supports our group focused mostly on mesoporous silica materials (MPs) for use in enzyme immobilization [39][40][41]. MPs have large surface areas with relatively large-pore diameters (5-100 nm) that match the sizes of the enzymes.…”
Section: Novel Enzyme Immobilization Methodsmentioning
confidence: 99%
“…Ideal properties for immobilization support include chemical and mechanical stability, hydrophilicity, inertness toward enzymes, ease of derivatization, biocompatibility, resistance to microbial attack, and a large surface area. Among the many organic and inorganic supports our group focused mostly on mesoporous silica materials (MPs) for use in enzyme immobilization [39][40][41]. MPs have large surface areas with relatively large-pore diameters (5-100 nm) that match the sizes of the enzymes.…”
Section: Novel Enzyme Immobilization Methodsmentioning
confidence: 99%
“…The problem is the necessity of having at least a primary amino group near the area involved in the immobilization., in In a recent paper it has been shown that this may (Figure 17) (Rueda et al, 2014). In other papers, amino-phenyl silicates were used to immobilize the lipases from C. antarctica (form B) (Boros et al, 2013) and Burkholderia cepacia (Abaházi et al, 2014). After adsorption, the immobilized enzymes were treated with glycerol diglycidyl ether to have some enzyme-support crosslinking.…”
Section: One-step Immobilization-purification Of Poly-lys Tagged Protmentioning
confidence: 99%
“…Immobilization was suggested to proceed via interfacial activation (activity improved after immobilization), and the final covalent attachments improve enzyme stability (Abaházi et al, 2014, Boros et al, 2013 This kind of heterofunctional hydrophobic supports may greatly improve the prospects of using interfacial activation of lipases as a tool to prepare biocatalysts useful under any experimental conditions, using the hydrophobic groups to have the a selective adsorption, and the other groups to transform this in an irreversible immobilization. The change of reversible to irreversible immobilization means that the support cannot be reused, therefore the strategy is only recommended when the improvement in enzyme stability or the prevention of enzyme release to the reaction medium are really relevant.…”
Section: One-step Immobilization-purification Of Poly-lys Tagged Protmentioning
confidence: 99%
“…Esters could be obtained with a conversion of 46.8% and enantiomeric excess of product (ee p ) > 99%. 9 Zhang et al 10 immobilized CaLB in ZnO nanowires introduced into macroporous SiO 2 and the supported lipase could be reused fifteen times without significant losses. (R)-2-Octanol acetate was obtained with a conversion of 49.1% and ee p of 99%.…”
Section: Introductionmentioning
confidence: 99%